The effect of Medicare eligibility on spousal insurance coverage - Marcus Dillender; Karen Mulligan (W.E. Upjohn Institute for Employment Research, 2015)
A majority of married couples in the United States take advantage of the fact that employers often provide health insurance coverage to spouses. When the older spouses become eligible for Medicare, however, many of them can no longer provide their younger spouses with coverage. In this paper, we study how spousal eligibility for Medicare affects the health insurance and health care access of the younger spouse. We find spousal eligibility for Medicare results in the younger spouse having worse insurance coverage and reduced access to health care services.
Keywords: I13; J3; 330; Health Insurance; Medicare; Individual Market; Marriage; Employer Benefits; ACA